2008
DOI: 10.1007/bf03256276
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variability of Methadone Response

Abstract: Methadone, an opioid analgesic, is used clinically in pain therapy as well as for substitution therapy in opioid addiction. It has a large interindividual variability in response and a narrow therapeutic index. Genetic polymorphisms in genes coding for methadone-metabolizing enzymes, transporter proteins (p-glycoprotein; P-gp), and mu-opioid receptors may explain part of the observed interindividual variation in the pharmacokinetics and pharmacodynamics of methadone. Cytochrome P450 (CYP) 3A4 and 2B6 have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 143 publications
1
78
0
Order By: Relevance
“…The elimination half-life of methadone ranges from 5 to 130 h, with a mean value of 22 h (37). The pharmacokinetics of methadone encompasses extreme inter-individual variability attributed to factors such as, age, co-administered medications, disease, ethnicity (due to differing allelic frequency of genetic polymorphisms), gender and weight (8,27,36). In a previous study, Richards-Waugh et al (36) demonstrated that an increasing number of SNPs present in CYP3A4 was associated with an increasing blood level of methadone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination half-life of methadone ranges from 5 to 130 h, with a mean value of 22 h (37). The pharmacokinetics of methadone encompasses extreme inter-individual variability attributed to factors such as, age, co-administered medications, disease, ethnicity (due to differing allelic frequency of genetic polymorphisms), gender and weight (8,27,36). In a previous study, Richards-Waugh et al (36) demonstrated that an increasing number of SNPs present in CYP3A4 was associated with an increasing blood level of methadone.…”
Section: Discussionmentioning
confidence: 99%
“…According to the most recent Centers for Disease Control and Prevention report, methadone accounts for >30% of prescription opioid deaths, while it only represents 2% of all opioid prescriptions (http://www.cdc.gov/vitalsigns/MethadoneOverdoses/index.html, last accessed on August, 2016). Much of the inter-individual variability in methadone pharmacokinetics may be due to genetic variations within the genes encoding CYP enzymes responsible for the metabolism of methadone (27).…”
Section: Introductionmentioning
confidence: 99%
“…44 This is quite interesting because CYP2B6 and CYP3A4 are the main isoforms involved in metabolizing methadone and sibutramine (CYP2B6 only), and it is thought that part of the individual response to these drugs depends on genetic variants of these cytochromes. [45][46][47] The recent results of genetic association tests for CYP2D6, CYP2B6 and CYP2C19 variations are presented in Table 1.…”
Section: Cytochrome P450mentioning
confidence: 99%
“…These statistics are presumably due to the use of methadone in the management of various pain conditions rather than in the treatment of addiction (Kharasch et al, 2009). Despite all of the negative attention methadone has received on the basis of these statistics, it is a very useful drug with unique pharmacological properties, including its high potency and efficacy, high oral bioavailability, no known formation of biologically active metabolites, and faster onset than morphine (Clark, 2008;Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The large interindividual variability that has been observed in response to methadone treatment has been attributed to genetic polymorphisms in the genes coding for P450s involved in methadone metabolism as well as to the polymorphisms in the transporter proteins and -opioid receptors (Li et al, 2008;Bunten et al, 2011).…”
Section: Introductionmentioning
confidence: 99%